PENGARUH KINERJA KEUANGAN PERUSAHAAN DAN OPINI AUDIT TAHUN SEBELUMNYA TERHADAP OPINI AUDIT MENGENAI GOING - Setiyanti, Sri Wiranti (JURNAL STIE SEMARANG, 2010)
Companies  that receive a going-concern  opinion  in the previous  year  wen more  likely  to receive  the same  opinion  on the current  year.  Ramadhani   (2004) proved  that the going-concern   audit  opinion  received  the previous  year  positive impact on acceptance  going-concern  audit opinion for  the year.  If previous  years the auditor  has issued  a going-concern   audit  opinion,  the auditors  will  be more likely to issue going  concern audit opinions again next year